Characterization of recombinant human lysosomal beta-hexosaminidases produced in the methylotrophic yeast Pichia pastoris - Espejo Mojica, Angela Johana; Institute for the Study of Inborn Errors of Metabolism, School of Sciences, Pontificia Universidad Javeriana. Bogotá, Colombia (Pontificia Universidad Javeriana, 2016)
β-hexosaminidases (Hex) are dimeric enzymes involved in the lysosomal degradation of glycolipids and glycans. They are formed by α- and/or β-subunits encoded by HEXA and HEXB genes, respectively. Mutations in these genes lead to Tay Sachs or Sandhoff diseases, which are neurodegenerative disorders caused by the accumulation of non-degraded glycolipids. Although tissue-derived Hex have been widely characterized, limited information is available for recombinant β-hexosaminidases. In this study, human lysosomal recombinant Hex (rhHex-A, rhHex-B, and rhHex-S) were produced in the methylotrophic yeast Pichia pastoris GS115. The highest specific enzyme activities were 13,124 for rhHexA; 12,779 for rhHex-B; and 14.606 U.mg-1 for rhHex-S. These results were 25- to 50-fold higher than those obtained from normal human leukocytes. Proteins were purified and characterized at different pH and temperature conditions. All proteins were stable at acidic pH, and at4 °C and 37 °C. At 45 °C rhHex-S was completely inactivated, while rhHex-A and rhHex-B showed high stability. This study demonstrates P. pastoris GS115 potential for polymeric lysosomal enzyme production, and describes the characterization of recombinant β-hexosaminidases produced within the same host.